Development of reverse-transcriptase quantitative PCR assays for detection of the cytokines IL-1β, TNF-α, and IL-10 in chelonians. (July 2019) - Rayl, Jeremy M.; Wellehan, James F.X.; Bunick, David; Allender, Matthew C.
Highlights: An effective and sensitive RT-qPCR assay was developed for turtle cytokine mRNA. Targets included IL-1β, TNFα, IL-10 and the reference gene β-actin. 85–110% efficiency, R 2 > 0.98, and limits of detection of 10–100 copies/reaction. Novel in vivo technique in chelonians to evaluate host innate immune response. Abstract: In response to viral pathogens, a host releases pro-inflammatory cytokines such as interleukin-1 beta (IL-1β) and tumor necrosis factor alpha (TNF-α) and anti-inflammatory cytokines such as interleukin-10 (IL-10). While several approaches exist to measure cytokine responses, evaluating gene transcription through reverse transcription quantitative polymerase chain reaction (RT-qPCR) provides a fast, reproducible, and sensitive method for quantifying this response. The objective of this study was to develop an effective and sensitive RT-qPCR assay for the quantification of red-eared slider ( Trachemys scripta elegans ) and eastern box turtle ( Terrapene carolina carolina ) cytokines: IL-1β, TNFα, IL-10 and the reference gene β-actin. RNA was isolated from the buffy coat layer of whole blood, comprised mainly of circulating leukocytes, and complimentary DNA (cDNA) was produced. Conventional PCR was performed to obtain cytokine mRNA sequences, products were sequenced, and a hydrolysis probe-based RT-qPCR assay was designed for each cytokine. Standard curves were generated using the target gene sequences cloned within a plasmid. Efficiencies for each assay were between of 85–110%, R 2 > 0.98, and limits of detection of 10–100 copies per reaction. The initial samples used to identify the novel target sequences were then used to evaluate the performance of the qPCR assays. Consistent transcription of beta actin across individuals in both species and measurable transcription of IL-1β, TNF-α, and IL-10 transcript targets in individuals of both species were observed. The assays are a novel technique in chelonians to evaluate host innate immune response.